Job Stress and its Influence on the Doctor’s Performance in the Public Hospital of Peshawar City, Pakistan - Ullah, Waseeq; Jabeen Shah, Syeda Farhana; Ahmad, Waqar (Journal of Gandhara Medical and Dental Science, 2017)
The study aims to find the influence of the job stress on the doctor’s performance in the public hospitals of Peshawar city. No doubt the profession of doctors is very respectable and they are doing a good work serving the people of society but their work environment must have some sort of influence on their performance as well. That’s why this study was taken in to consideration to study the doctors’ performance in the public hospitals. This study was designed to assess the doctor’s performance in public hospitals only. Sample size was drawn on the basis of simple random sampling technique as the data was of quantitative in nature. Data was collected through a questionnaire which was developed by the research himself and to find the reliability and validity a pilot test was done with the data collection tool which showed some mistakes and those mistakes were rectified. Due to limited time period and resources of the researcher, the researcher has drawn 150 sample size of the total population of the doctors in the public hospitals of Peshawar city. A total of 150samples (50 from each public hospitals respectively of Peshawar) data were collected .Out of 150 study participants; it was observed that doctors in KTH, LRH and HMC were suffering from job stress collectively. Their performance was affected and the result of this study highlight the significant result in which it was concluded that job stress had a negative impact on the doctor’s performance in the public hospitals of Peshawar.